Lithium ion sieve hydrogel with dual performance and preparation method and application thereof
By combining the hydrogel with the lithium ion sieve, lithium ion sieve hydrogel is prepared, which solves the problems of powdery, poor recovery and high manganese loss after the lithium ion sieve molding, and achieves high lithium adsorption performance, stability and Improved mechanical performance.
Patent Information
- Application Number
- CN202510052185.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-02-18
AI Technical Summary
As lithium-ion adsorbents, the existing lithium-ion sieve is powdery after forming, with poor recycling effect and easy to lead to high manganese loss, limiting its industrialization process.
By combining the hydrogel with the prepared lithium ion sieve, lithium ion sieve hydrogel is prepared. The deviceization of the hydrogel and the polymer dual network structure are used to significantly enhance the stability and adsorption capacity of the lithium ion sieve. .
Lithium ion sieve hydrogel has the advantages of high lithium adsorption performance, low solvent loss, high stability, excellent mechanical properties, and convenient and fast use and recycling, and has a long service life.
Smart Images

Figure CN119455922A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium adsorbents, and specifically relates to a lithium ion sieve hydrogel with dual properties and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] In recent years, the new energy industry has developed rapidly. As a key component, the demand for lithium resources is expected to increase significantly. Therefore, the importance of developing lithium resources and finding alternatives has become increasingly prominent. Most of the world's lithium resources exist in salt lake brine, and extracting lithium from salt lake brine has become an important direction. At present, the main technologies for extracting lithium from salt lake brine include precipitation, solvent extraction, membrane separation and adsorption. Among them, the adsorption method is considered to be one of the most promising methods due to its high efficiency and low cost. The core of the adsorption method lies in the selection of suitable adsorbents. Inorganic ion adsorbents are widely favored due to their excellent selectivity and high efficiency. Among them, lithium ion sieve (LIS) has the advantages of low toxicity, low cost, high chemical stability, etc., and is a very potential lithium ion adsorption material.
[0004] Lithium ion sieve (LIS) is a typical adsorbent with the advantages of simple preparation, low cost and environmental friendliness. Its unique pore structure and "ion sieving" characteristics make it have excellent adsorption effect and selectivity for lithium ions. Although LIS has good adsorption capacity, it is powdery after molding, has poor recovery effect and easily leads to high manganese dissolution, which limits its industrialization process. To solve this problem, some scholars have suggested using granulation, film forming, foaming or gel methods to make lithium ion sieves into devices for industrial application. However, these methods will reduce the contact area with lithium ions, thereby reducing the adsorption sites and affecting their performance.
[0005] Therefore, there is an urgent need in the art to provide a new lithium adsorbent, so that the adsorption capacity and cycle stability of the prepared lithium ion adsorbent are improved, and the adsorbent has good processability and stability in use, and the preparation method is simple and convenient. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a lithium ion sieve hydrogel with dual properties and its preparation method and application. By compounding the hydrogel with the prepared lithium ion sieve, the lithium ion sieve hydrogel prepared by the present invention has high lithium adsorption performance, low dissolution loss, high stability, excellent mechanical properties, and convenient and fast use and recycling, and further has the advantages of long service life.
[0007] Specifically, the technical solution of the present invention is as follows: In a first aspect of the present invention, a lithium ion sieve hydrogel with dual properties is provided, wherein the lithium ion sieve hydrogel comprises a lithium ion sieve and a hydrogel bonded to the lithium ion sieve via a metal ion coordination bond; the lithium ion sieve is composed of lithium hydroxide monohydrate, manganese trioxide and a metal source; the hydrogel is composed of acrylic acid, acrylamide, chitosan, a crosslinking agent and an initiator; Wherein, the metal source is selected from one or more of an aluminum source, an iron source and an aluminum-iron mixed metal source; preferably, the aluminum source is selected from one or more of aluminum hydroxide, aluminum oxide and aluminum chloride, and the iron source is selected from one or more of ferric sulfate, ferric chloride and ferric chloride hexahydrate; further preferably, the aluminum source is aluminum chloride, and the iron source is ferric chloride.
[0008] The second aspect of the present invention provides a method for preparing the above-mentioned lithium ion sieve hydrogel with dual properties, comprising the following steps: S1, mixing manganese trioxide, lithium hydroxide monohydrate and metal source in deionized water, performing hydrothermal reaction, and drying and calcining the obtained intermediate product in sequence to obtain a lithium ion sieve precursor; S2, washing the lithium ion sieve precursor with an acidic solution, and filtering to obtain the lithium ion sieve; S3, dispersing the lithium ion sieve into a mixed solution of acrylic acid, acrylamide, chitosan, a crosslinking agent and an initiator, and performing a heating reaction to obtain a lithium ion sieve hydrogel.
[0009] Preferably, in step S1, the molar ratio of the manganese trioxide, lithium hydroxide monohydrate and the metal source is 1:2-2.4:0.02-0.05.
[0010] Preferably, in step S1, the temperature of the hydrothermal reaction is 180-260° C., and the time is 4-24 h; further preferably, the temperature of the hydrothermal reaction is 200° C., and the time is 8 h.
[0011] Preferably, in step S1, the drying temperature is 100-150°C, and the time is 1-6 h; the calcination temperature is 400-600°C, and the time is 4-24 h; further preferably, the drying temperature is 120°C, and the time is 2 h; the calcination temperature is 450°C, and the time is 6 h.
[0012] Preferably, in step S2, the acidic solution is selected from dilute hydrochloric acid, the concentration of the dilute hydrochloric acid is 0.5~2 mol / L, and the molar ratio of the dilute hydrochloric acid to the lithium ion sieve precursor is 2:1; the washing time is 1~12 h; further preferably, the concentration of the dilute hydrochloric acid is 0.5 mol / L; the washing time is 4 h.
[0013] Preferably, in step S3, the mass ratio of the lithium ion sieve, acrylic acid, acrylamide, chitosan, cross-linking agent and initiator is 0.5~1.5:1.5~2.5:1.5~2.5:1.5~2.5:0.04~0.08:0.01~0.04; further preferably, the mass ratio of the lithium ion sieve, acrylic acid, acrylamide, chitosan, cross-linking agent and initiator is 1:2:2:2:0.06:0.03.
[0014] Preferably, in step S3, the crosslinking agent is selected from one or more of 1,4-cyclohexanedimethanol divinyl ether, p-divinylbenzene, and N,N'-methylenebisacrylamide; and the initiator is selected from one or more of ammonium persulfate, potassium persulfate, and cumene hydroperoxide.
[0015] More preferably, the cross-linking agent is N,N'-methylenebisacrylamide; and the initiator is ammonium persulfate.
[0016] Preferably, in step S3, the temperature of the heating reaction is 50-80°C, and the time is 2-12 h; further preferably, the temperature of the heating reaction is 60°C, and the time is 6 h.
[0017] The third aspect of the present invention provides an application of the dual-performance lithium ion sieve hydrogel described in the first aspect and / or the dual-performance lithium ion sieve hydrogel prepared by the preparation method described in the second aspect in lithium extraction technology.
[0018] One or more embodiments of the present invention have at least the following beneficial effects: (1) The lithium ion sieve hydrogel prepared by the present invention is prepared by using ions of the same valence state but different sizes (Al 3+ , Fe 3+ etc.) to replace part of the manganese ions (Mn 3+ ), which makes the crystal structure of the ion sieve more stable and the ion channel more spacious (the ionic radius of Al and Fe are smaller than that of Mn ions), so it has higher lithium ion adsorption capacity and stability, and can still maintain high adsorption capacity and stability in multiple cycles of adsorption-desorption, and will not lose the ability to adsorb lithium ions due to the dissolution of the lithium ion sieve.
[0019] (2) The present invention integrates powdered lithium ion sieve into a device through hydrogel, and utilizes the interaction between the hydrogel device and the metal ion coordination bonds between the ion sieve to significantly inhibit the loss of manganese ions due to dissolution of the ion sieve, thereby greatly enhancing the stability of the ion sieve. At the same time, because the structure of the gel improves the surface of the ion sieve, more adsorption sites are exposed, and the construction of the hydrogel structure greatly improves the adsorption capacity.
[0020] (3) The lithium ion sieve hydrogel prepared by the present invention significantly enhances the structure of the hydrogel device by utilizing the device scheme of the hydrogel and the structure of the polymer double network. At the same time, the different groups on the double network can not only effectively alleviate the agglomeration of the ion sieve but also form hydrogen bonds to further constrain the ion sieve, so that the lithium ion sieve has a large surface area in the hydrogel while also having an integral structure. Therefore, it has excellent recycling ability and service life. In the face of complex use environments, the morphology of the device can be kept intact, making it easy to use and recycle.
[0021] (4) Carboxyl groups and metal ions (Al 3+ , Fe 3+ ) can form metal ion coordination bonds, which can inhibit Jahn-Taller distortion and constrain the elements on the precursor. That is, the present invention can adjust the amount of acrylic acid added so that the ion sieve can fully play the role of strengthening the skeleton in the hydrogel network, thereby improving the mechanical properties of the material and having application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0023] Figure 1 This is a scanning electron microscope image (SEM) of HMnAlO prepared in Example 1 of the present invention; Figure 2 This is a scanning electron microscope image of HMnFeO prepared in Example 2 of the present invention; Figure 3 This is a scanning electron microscope image of HMnAlFeO prepared in Example 3 of the present invention; Figure 4 This is a scanning electron microscope image of HMnO prepared in Comparative Example 1 of the present invention; Figure 5 This is a scanning electron microscope image of PAC-HMnAlFeO prepared in Example 3 of the present invention; Figure 6 X-ray diffraction patterns (XRD) of HMnAlFeO and PAC-HMnAlFeO prepared in Example 3 of the present invention; Figure 7 The mass loss rate variation diagram of lithium ion sieves doped with different metals prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3; Figure 8 The mass loss rate variation diagram of lithium ion sieve hydrogels doped with different metals prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3; Fig. 9The stress-strain curves of lithium ion sieve hydrogels doped with different metals prepared in Examples 1 to 3 of the present invention and Comparative Example 1; Fig.10 The stress-strain curves of lithium ion sieve hydrogels doped with different amounts of acrylic acid prepared in Comparative Examples 19 to 21 of the present invention. DETAILED DESCRIPTION
[0024] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0025] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0026] Embodiment 1: This embodiment provides a lithium ion sieve hydrogel with dual properties and a preparation method thereof, which specifically comprises the following steps: (1) First, weigh 3 g of manganese trioxide, 1.603 g of lithium hydroxide monohydrate, and 0.076 g of aluminum chloride, and grind them thoroughly in an agate mortar until they are completely fine and free of particles.
[0027] (2) The mixed materials in step (1) were transferred to a hydrothermal reactor with a capacity of 100 mL and reacted in an oven at 200° C. for 8 h to generate the intermediate product LiMnO2.
[0028] (3) The generated LiMnO2 was taken out from the reactor, dried at 120 °C for 2 h, and then ground until there were no particles.
[0029] (4) The prepared LiMnO2 was placed in a muffle furnace again and calcined at 450 °C for 6 h to obtain the lithium ion sieve precursor Li 1.6 Mn 1.6 O4.
[0030] (5) The lithium ion sieve precursor was pickled with a 0.5 mol / L hydrochloric acid solution for 4 h to obtain the product lithium ion sieve HMnAlO.
[0031] (6) Add 1 g HMnAlO to a solution containing 2 g acrylic acid, 2 g acrylamide, and 2 g chitosan, stir evenly, add 0.06 g ammonium persulfate and 0.03 g N,N'-methylenebisacrylamide, pour the solution into a mold, and wait for gelation at 60 °C for 6 h to obtain the lithium ion sieve hydrogel PAC-HMnAlO.
[0032] Embodiment 2: This embodiment provides a lithium ion sieve hydrogel with dual properties and a preparation method thereof, which specifically comprises the following steps: (1) First, weigh 3 g of manganese trioxide, 1.603 g of lithium hydroxide monohydrate, and 0.092 g of ferric chloride, and grind them thoroughly in an agate mortar until they are completely fine and free of particles.
[0033] (2) The mixed materials in step (1) were transferred to a hydrothermal reactor with a capacity of 100 mL and reacted in an oven at 200° C. for 8 h to generate an intermediate product, LiMnFeO2.
[0034] (3) The generated LiMnFeO2 was taken out from the reactor, dried at 120 °C for 2 h, and then ground until there were no particles.
[0035] (4) The prepared LiMnFeO2 was placed in a muffle furnace again and calcined at 450 °C for 6 h to obtain the precursor Li 1.6 Mn 1.2 Fe 0.4 O4.
[0036] (5) The precursor was pickled with a 0.5 mol / L hydrochloric acid solution for 4 h to obtain the product lithium ion sieve HMnFeO.
[0037] (6) Add 1 g HMnFeO to a solution containing 2 g acrylic acid, 2 g acrylamide, and 2 g chitosan, stir evenly, add 0.06 g ammonium persulfate and 0.03 g N,N'-methylenebisacrylamide, pour the solution into a mold, and wait for gelation at 60 °C for 6 h to obtain the lithium ion sieve hydrogel PAC-HMnFeO.
[0038] Embodiment 3: This embodiment provides a lithium ion sieve hydrogel with dual properties and a preparation method thereof, which specifically comprises the following steps: (1) First, weigh 3 g of manganese trioxide, 1.603 g of lithium hydroxide monohydrate, 0.046 g of ferric chloride, and 0.038 g of aluminum chloride, and grind them thoroughly in an agate mortar until they are completely fine and free of particles.
[0039] (2) The mixed materials in step (1) were transferred to a hydrothermal reactor with a capacity of 100 mL and reacted in an oven at 200° C. for 8 h to generate LiMnO2.
[0040] (3) The generated LiMnAlFeO2 is taken out from the reactor, dried at 120°C, and then ground until there are no particles.
[0041] (4) The prepared LiMnAlFeO2 was placed in a muffle furnace again and calcined at 450 °C for 6 h to obtain the precursor Li 1.6 Mn 1.6 O4.
[0042] (5) The precursor was pickled with a 0.5 mol / L hydrochloric acid solution for 4 h to obtain the product lithium ion sieve HMnAlFeO.
[0043] (6) Add 1 g HMnAlFeO to a solution containing 2 g acrylic acid, 2 g acrylamide, and 2 g chitosan, stir evenly, add 0.06 g ammonium persulfate and 0.03 g N,N'-methylenebisacrylamide, pour the solution into a mold, and wait for gelation at 60 °C for 6 h to obtain the lithium ion sieve hydrogel PAC-HMnAlFeO.
[0044] Embodiment 4: This example tests the structural characteristics of the lithium ion sieve and hydrogel structure prepared in Examples 1 to 3 and Comparative Example 1. like Figures 1 to 4 As shown, the scanning electron microscope images of the lithium ion sieves prepared in Examples 1 to 3 and Comparative Example 1 respectively show that, compared with Comparative Example 1, in Examples 1 to 3, as the aluminum source and the iron source increase, the shape of the lithium ion sieve is not destroyed, and the size is reduced, showing a larger surface area (as can be seen from the scale in the figure).
[0045] like Figure 5 As shown, this is a scanning electron microscope image of the lithium ion sieve hydrogel prepared in Example 3. It can be seen that the ion sieves are distributed on the network nodes of the hydrogel, exposing a larger surface area, which can serve as physical cross-linking points to significantly enhance the mechanical strength of the lithium ion sieve hydrogel.
[0046] like Figure 6 As shown in the figure, it can be seen from the XRD pattern analysis that according to the analysis of the peak position and peak intensity of the XRD of the manganese lithium ion sieve, it is consistent with the Li 1.6 Mn 1.602 The most consistent one belongs to the space group of Fd-3m, and the doping of aluminum source and iron source has no effect on the structure of manganese-based ion sieve; at the same time, the peaks of gel material and manganese-based lithium ion sieve were observed, which further proves that the structure of hydrogel does not destroy the crystal structure of manganese-based lithium ion sieve.
[0047] Comparative Example 1: This comparative example provides a lithium ion sieve hydrogel and a preparation method thereof, which specifically comprises the following steps: (1) First, accurately weigh 3 g of manganese trioxide and 1.603 g of lithium hydroxide monohydrate and grind them thoroughly in an agate mortar until they are completely fine and free of particles.
[0048] (2) The mixed materials in step (1) were transferred to a hydrothermal reactor with a capacity of 100 mL, deionized water was added to 4 / 5 of the reactor, and the reaction was continued in an oven at 200°C for 8 h to generate the intermediate product LiMnO2.
[0049] (3) Take the generated LiMnO2 out of the reactor: first suck out the supernatant with a rubber-tipped dropper, then take out the precipitate, rinse the residue in the reactor into the beaker where the precipitate is placed, dry it at 120°C for 2 h, and then grind it until there are no particles.
[0050] (4) The prepared LiMnO2 was placed in a muffle furnace again and calcined at 450 °C for 6 h to obtain the precursor Li 1.6 Mn 1.6 O4.
[0051] (5) Finally, the precursor was pickled with 0.5 mol / L hydrochloric acid solution for 4 h to obtain the product lithium ion sieve HMnO, the scanning electron microscope image of which is shown in Figure 5 shown.
[0052] (6) Add 1 g HMnO to a solution containing 2 g acrylic acid, 2 g acrylamide, and 2 g chitosan, stir evenly, add 0.06 g ammonium persulfate and 0.03 g N,N'-methylenebisacrylamide, pour the solution into a mold, and wait for gelation at 60 °C for 6 hours to obtain the lithium ion sieve hydrogel PAC-HMnO.
[0053] Comparative Example 2: This comparative example provides a lithium ion sieve hydrogel and a preparation method thereof, which specifically comprises the following steps: (1) First, accurately weigh 3 g of manganese trioxide and 1.603 g of lithium hydroxide monohydrate and grind them thoroughly in an agate mortar until they are completely fine and free of particles.
[0054] (2) Transfer the mixed materials in step (1) to a 100 mL beaker, add 50 g of water and stir thoroughly, then remove the water by rotary evaporation at 70 °C.
[0055] (3) The obtained mixture was placed in a muffle furnace again and calcined at 500 °C for 6 h to obtain the precursor Li 1.6 Mn 1.6 O4-G1.
[0056] (4) Finally, the precursor was pickled with a 0.5 mol / L hydrochloric acid solution for 4 h to obtain the product lithium ion sieve HMnO-G1.
[0057] (5) Add 1 g HMnO-G1 to a solution of 2 g acrylic acid, 2 g acrylamide, and 2 g chitosan, stir evenly, add 0.06 g ammonium persulfate and 0.03 g N,N'-methylenebisacrylamide, pour the solution into a mold, and wait for gelation at 60 °C for 6 h to obtain the lithium ion sieve hydrogel PAC-HMnO-G1.
[0058] Comparative Example 3: This comparative example provides a lithium ion sieve hydrogel and a preparation method thereof, which specifically comprises the following steps: (1) First, accurately weigh 4.392 g of manganese carbonate and 1.603 g of lithium hydroxide monohydrate and grind them thoroughly in an agate mortar until they are completely fine and free of particles.
[0059] (2) Transfer the mixed materials in step (1) to a 100 mL beaker, add 50 g of water and stir thoroughly, then remove the water by rotary evaporation at 70 °C.
[0060] (3) The obtained mixture was placed in a muffle furnace again and calcined at 500 °C for 6 h to obtain the precursor Li 1.6 Mn 1.6 O4-G2.
[0061] (4) Finally, the precursor was pickled with a 0.5 mol / L hydrochloric acid solution for 4 h to obtain the product lithium ion sieve HMnO-G2.
[0062] (5) Add 1 g HMnO-G2 to a solution of 2 g acrylic acid, 2 g acrylamide, and 2 g chitosan, stir evenly, add 0.06 g ammonium persulfate and 0.03 g N,N'-methylenebisacrylamide, pour the solution into a mold, and wait for gelation at 60 °C for 6 h to obtain the lithium ion sieve hydrogel PAC-HMnO-G2.
[0063] Comparative Examples 4 to 8: The difference between Comparative Examples 4 to 8 and Example 1 is that the amount of aluminum chloride added in step (1) is different. In Example 1, the amount of metal source aluminum chloride added accounts for 3%, while the amounts of metal source aluminum chloride added in Comparative Examples 4 to 8 account for 1%, 2%, 4%, 5%, and 6%, respectively. The contents of other components and the preparation method are consistent with those in Example 1.
[0064] Comparative Examples 9 to 13: The difference between Comparative Examples 9 to 13 and Example 2 is that the amount of ferric chloride added in step (1) is different. In Example 2, the amount of metal source ferric chloride added accounts for 3%, and the amount of metal source ferric chloride added in Comparative Examples 9 to 13 accounts for 1%, 2%, 4%, 5%, and 6%, respectively. The contents of other components and the preparation method are consistent with those in Example 2.
[0065] Comparative Examples 14 to 18: The difference between Comparative Examples 14 to 18 and Example 3 is that the amounts of aluminum chloride and ferric chloride added in step (1) are different. In Example 3, the amount of aluminum chloride and ferric chloride added as the metal source accounts for 3%, while the amounts of aluminum chloride and ferric chloride added as the metal source accounts for 1%, 2%, 4%, 5% and 6% in Comparative Examples 14 to 18, respectively. The contents of other components and the preparation method are consistent with those in Example 3.
[0066] Comparative Examples 19-21: The difference between Comparative Examples 19 to 21 and Example 3 is that in step (6), the amount of acrylic acid added is different. In Example 3, the amount of acrylic acid added is 2 g, and the mass ratio of acrylic acid to acrylamide is 1:1. The mass ratios of acrylic acid added to acrylamide in Comparative Examples 19 to 21 are 2:1, 3:1, and 4:1, respectively. The contents of other components and the preparation method are consistent with those in Example 3.
[0067] Test Example 1: This test example investigates the ability of lithium ion sieves (lithium adsorbents 1-6) doped with different metals prepared in Examples 1-3 and Comparative Examples 1-3 to adsorb lithium ions in brine, specifically testing the cyclic adsorption effect on lithium ions under the same conditions.
[0068] Experimental process: Weigh 0.5 g of lithium adsorbent, suspend the adsorbent in 50 mL of lithium chloride solution (the concentration of lithium chloride solution is 500 mg / L), adsorb for 3-5 hours at 40-50 °C until adsorption equilibrium is reached, filter the supernatant with a 0.1 μm filter membrane, and use ICP-OES inductively coupled plasma emission spectrometer to detect the lithium ion content. The Li + Adsorption amount:
[0069] Where q t is the adsorption capacity at time t, mg / g; C0 is the initial mass concentration of lithium ions in the solution, mg / L; C t is the mass concentration of lithium ions after adsorption, mg / L; m is the mass of the adsorbent, g; V is the volume of the adsorption liquid, L.
[0070] The specific test data are shown in Table 1: Table 1
[0071] It can be seen from the data in Table 1 that, compared with Comparative Example 1, Example 1 or Example 2 of the present invention performs metal doping (using Al / Fe ions to replace part of the manganese ions), and the addition of the metal source greatly increases the adsorption capacity and stability of the ion sieve, among which the synergistic effect of the simultaneous addition of the aluminum source and the iron source on the adsorption capacity and stability improvement is particularly significant (Example 3). This is because the ion valence of the aluminum source and the iron source is relatively stable and will not undergo disproportionation, and the average valence of the ion valence of the precursor is increased, which can show stronger stability and adsorption capacity.
[0072] From the comparison of the data of Comparative Examples 1 and 2, it can be seen that the preparation method of the present invention using water bath heating and calcination together has a better cyclic adsorption effect on the lithium ion sieve than the single calcination method; from the comparison of the data of Comparative Examples 2 and 3, it can be seen that under the same preparation method (single calcination method), the difference in manganese source does not affect the cyclic adsorption effect of the lithium ion sieve.
[0073] Test Example 2: This test example explores the ability of lithium ion sieve hydrogels doped with different metal source doping amounts prepared in Examples 1 to 3 and Comparative Examples 4 to 18 to adsorb lithium ions in brine. Specifically, the adsorption effect of lithium ions was tested under the same conditions. The experimental process is consistent with the test example. The results are shown in Table 2: Table 2
[0074] From the comparison of the data in Table 2, it can be seen that the amount of metal source added has a certain influence on the lithium ion adsorption capacity. The lithium ion sieve hydrogel prepared in Examples 1 to 3 of the present invention has the largest adsorption capacity for lithium ions. Lower than or higher than the amount of metal source added (3%) set in the present invention will affect the adsorption of lithium ions. It can be directly seen from the data that when the addition amount exceeds 5%, the adsorption amount of lithium ions has been greatly reduced.
[0075] Test Example 3: This test example investigates the ability of lithium ion sieve hydrogels (lithium adsorbents 7-12) doped with different metals prepared in Examples 1-3 and Comparative Examples 1-3 to adsorb lithium ions in brine, specifically testing the cyclic adsorption effect on lithium ions under the same conditions.
[0076] Experimental process: Weigh 0.5 g of lithium adsorbent, suspend the adsorbent in 50 mL of lithium chloride solution (the concentration of lithium chloride solution is 500 mg / L), adsorb for 3-5 hours at 40-50 °C until adsorption equilibrium is reached, filter the supernatant with a 0.1 μm filter membrane, and use ICP-OES inductively coupled plasma emission spectrometer to detect the lithium ion content. The Li + Adsorption amount:
[0077] Where q t is the adsorption capacity at time t, mg / g; C0 is the initial mass concentration of lithium ions in the solution, mg / L; C t is the mass concentration of lithium ions after adsorption, mg / L; m is the mass of the adsorbent, g; V is the volume of the adsorption liquid, L.
[0078] The specific test data are shown in Table 3: Table 3
[0079] From the comparison of the data in Table 1 and Table 3, it can be seen that the present invention prepares the lithium ion sieve into a lithium ion sieve hydrogel, and the lithium ion adsorption capacity is greatly improved; and from the comparison of the data in Comparative Example 1 in the two tables, it can be seen that when no doping with other metals is performed, the lithium ion sieve formed by a single manganese source and the lithium ion sieve hydrogel do not change much in the effect of lithium ion adsorption. This is because the addition of the hydrogel transforms the lithium ion sieve from a microscopic powder state into a macroscopic gel device, which cannot play the role of the present invention in improving the stability and adsorption capacity of the lithium ion sieve by using a strong coordination effect.
[0080] From the specific data analysis in Table 2, it can be seen that compared with Comparative Example 1, Example 1 or Example 2 of the present invention is metal doped (using Al / Fe to replace part of the manganese ions). The addition of the metal source greatly increases the adsorption amount and stability of the ion sieve hydrogel. At the same time, the carboxyl and Al in the hydrogel 3+ , Fe 3+ Ions are strong coordination bonds, so the ion exchange channels of ion sieves are more stable and efficient, greatly improving the adsorption efficiency and adsorption capacity.
[0081] From the comparison of the data of Comparative Examples 1 and 2, it can be seen that the preparation method of the present invention using a combination of water bath heating and calcination has a better cyclic adsorption effect on the lithium ion sieve hydrogel than the single calcination method. This is because the hydrothermal method can form a better dispersed phase and the prepared ion sieve has a larger surface area.
[0082] Test example 4: This test example investigates the mass loss rate of lithium ion sieves doped with different metals prepared in Examples 1 to 3 and Comparative Examples 1 to 3. Experimental procedure: Regeneration and reuse studies were performed in five consecutive adsorption-desorption cycles. In each cycle, the Li-ion sieve was added to 100 mL of 100 mg / L LiCl solution. After 24 h of shaking, the removed hydrogel was regenerated with 50 mL (0.5 M) HCl solution and washed with a large amount of deionized water to remove residual ions. After vacuum drying, the regenerated Li-ion sieve was subjected to the next adsorption cycle as before. Each cycle was started before the adsorbent was vacuum dried and weighed to verify its weight.
[0083] The results are as follows Figure 7 As shown, the mass loss rates of the lithium ion sieves prepared in Examples 1 to 3 of the present invention are 5.90%, 4.93%, and 2.42%, respectively; the mass loss rates of the lithium ion sieves prepared in Comparative Examples 1 to 3 of the present invention are 13.17%, 12.88%, and 12.63%, respectively. Compared with Comparative Examples 1 to 3, the mass loss rate of the lithium ion sieves in Examples 1 to 3 of the present invention is reduced by about 8.4%, which is because the addition of the metal source can reduce the disproportionation of trivalent manganese, thereby greatly inhibiting the mass loss rate of the lithium ion sieve.
[0084] Test Example 5: This test example investigates the mass loss rate of lithium ion sieve hydrogels doped with different metals prepared in Examples 1 to 3 and Comparative Examples 1 to 3. Experimental procedure: Regeneration and reuse were studied in five consecutive adsorption-desorption cycles. In each cycle, PAC-X hydrogel was added to 100 mL of 100 mg L -1 LiCl solution. After shaking for 24 h, the hydrogel was taken out and regenerated with 50 mL (0.5 M) HCl solution and washed with a large amount of deionized water to remove residual ions. After vacuum drying, the regenerated hydrogel was subjected to the next adsorption cycle as before. Before the adsorbent was vacuum dried and weighed, each cycle was started to verify its weight.
[0085] The results are as follows Figure 8 As shown, the mass loss rates of the lithium ion sieve hydrogels prepared in Examples 1 to 3 of the present invention are 2.53%, 2.21%, and 0.38%; the mass loss rates of the lithium ion sieve hydrogels prepared in Comparative Examples 1 to 3 of the present invention are 10.62%, 11.02%, and 10.68%, respectively. Compared with the mass loss rate of the lithium ion sieve hydrogels in Comparative Examples 1 to 3, the mass loss rate is 10.3% less, which is not only due to the addition of the metal source to reduce the disproportionation of trivalent manganese, but also due to the strong coordination between the hydrogel and the lithium ion sieve, thereby greatly suppressing the mass loss rate of the lithium ion sieve.
[0086] Test Example 6: This test example investigates the mechanical properties of lithium ion sieve hydrogels doped with different metals prepared in Examples 1 to 3 and Comparative Examples 1 to 3 and Comparative Examples 19 to 21. Specifically, a stress-strain curve test is performed on the dumbbell-shaped lithium ion sieve hydrogel specimens doped with different metals under the same conditions using a universal testing machine.
[0087] The results are as follows Figure 8As shown, due to the strong coordination bond of the carboxylate, the lithium ion sieve hydrogel prepared in Examples 1 to 3 of the present invention can maintain a good morphology under certain external conditions compared to the single manganese-doped lithium ion sieve hydrogel (Comparative Example 1), and better meet the purpose of easy recycling and use.
[0088] Among them, the stresses of Examples 1 to 3 are 288.8 kPa, 226.8 kPa and 615.4 kPa, respectively, and the strains are 403.1%, 661.9% and 920.4%, respectively; the changes in Examples 1 to 3 show that the introduction of metal sources, especially the doping of bimetallic sources, significantly enhances the mechanical properties of lithium ion sieve hydrogels; compared with Comparative Example 1, the stress of Example 3 is increased by 6 times and the strain is increased by 3 times; this is because the carboxyl groups and metal ions (Al3+, Fe3+) in the hydrogel can form metal ion coordination bonds, which can inhibit Jahn-Taller distortion and constrain the elements on the precursor; At the same time, if Fig.10 As shown, the stresses of Comparative Examples 19 to 21 are 561.2 kPa, 349.2 kPa and 201.4 kPa, respectively, and the strains are 718%, 465% and 181%, respectively. Compared with Example 3, the amount of acrylic acid added in Comparative Examples 19 to 21 has changed, but the mechanical properties are obviously not as good as those in Example 3. This is because the amount of acrylic acid added has a certain effect on the coordination of metal ions. By adjusting the amount of acrylic acid added, the ion sieve can fully play the role of strengthening the skeleton in the hydrogel network, thereby improving the rigidity of the material.
[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A lithium ion sieve hydrogel with dual properties, characterized in that: The lithium ion sieve hydrogel comprises a lithium ion sieve and a hydrogel bonded to the lithium ion sieve through a metal ion coordination bond; the lithium ion sieve is composed of lithium hydroxide monohydrate, manganese trioxide and a metal source; the hydrogel is composed of acrylic acid, acrylamide, chitosan, a crosslinking agent and an initiator; Wherein, the metal source is selected from one or more of an aluminum source, an iron source and an aluminum-iron mixed metal source; the aluminum source is selected from one or more of aluminum hydroxide, aluminum oxide and aluminum chloride; the iron source is selected from one or more of ferric sulfate, ferric chloride and ferric chloride hexahydrate; The molar ratio of the manganese trioxide, lithium hydroxide monohydrate and the metal source is 1:2-2.4:0.02-0.05; The mass ratio of the lithium ion sieve, acrylic acid, acrylamide, chitosan, crosslinking agent and initiator is 0.5-1.5:1.5-2.5:1.5-2.5:1.5-2.5:0.04-0.08:0.01-0.04; The crosslinking agent is selected from one or more of 1,4-cyclohexanedimethanol divinyl ether, p-divinylbenzene, and N,N'-methylenebisacrylamide; the initiator is selected from one or more of ammonium persulfate, potassium persulfate, and cumene hydroperoxide.
2. A method for preparing a lithium ion sieve hydrogel with dual properties as claimed in claim 1, characterized in that: The steps include: S1, mixing manganese trioxide, lithium hydroxide monohydrate and metal source in deionized water, performing hydrothermal reaction, and drying and calcining the obtained intermediate product in sequence to obtain a lithium ion sieve precursor; S2, washing the lithium ion sieve precursor with an acidic solution, and filtering to obtain the lithium ion sieve; S3, dispersing the lithium ion sieve into a mixed solution of acrylic acid, acrylamide, chitosan, a crosslinking agent and an initiator, and performing a heating reaction to obtain a lithium ion sieve hydrogel.
3. The preparation method according to claim 2, characterized in that: In step S1, the temperature of the hydrothermal reaction is 180-260° C., and the time is 4-24 h.
4. The preparation method according to claim 2, characterized in that: In step S1, the drying temperature is 100-150°C, and the time is 1-6 h; the calcination temperature is 400-600°C, and the time is 4-24 h.
5. The preparation method according to claim 2, characterized in that: In step S2, the acidic solution is selected from dilute hydrochloric acid, the concentration of the dilute hydrochloric acid is 0.5-2 mol / L, and the molar ratio of the dilute hydrochloric acid to the lithium ion sieve precursor is 2:1; the washing time is 1-12 h.
6. The preparation method according to claim 2, characterized in that: In step S4, the heating reaction temperature is 50-80° C. and the time is 2-12 h.
7. Use of the dual-performance lithium ion sieve hydrogel according to claim 1 and / or the dual-performance lithium ion sieve hydrogel prepared by the preparation method according to any one of claims 2 to 6 in lithium extraction technology.
Citation Information
Patent Citations
Preparation method of lithium ion adsorption material
CN113731371A
Preparation method of cation-doped modified lithium ion sieve
CN116371387A
Preparation method of lithium ion sieve adsorbent
CN118002093A
Adsorption material for extracting lithium, preparation method and application
CN118594509A
Cited By
Efficient recovery method for valuable metals in waste lithium iron phosphate material
CN120464862A
An efficient method for recovering valuable metals from waste lithium iron phosphate materials
CN120464862B